Case report: Recovery of hallucinations and cognitive impairment after administration of donepezil in a patient with schizophrenia and carbon monoxide poisoning - Baek, Seon-Hwa; Kim, Ju-Wan; Lee, Yun Young; Kim, Ju-Yong; Kim, Sung-Wan; Kim, Jae-Min (Frontiers in Psychiatry, 2022)
Objectives This report aims to introduce a rare case of a dramatic recovery by donepezil with a patient with schizophrenia who suffered from remaining psychotic symptoms despite proper treatment and had a cognitive impairment by carbon monoxide (CO) poisoning sequelae. Case report A 38-year-old male who developed schizophrenia 2 years ago had attempted suicide via CO inhalation due to his uncontrolled symptoms. He was hospitalized with delayed neurological sequelae (DNS). Though hyperbaric oxygen therapy (HBOT) was applied 10 times, his cognitive impairment did not recover. Surprisingly, with 5–10 mg donepezil, both cognitive function and the psychotic symptoms of the patient remarkably improved. Conclusion This case showed a good response of donepezil for a patient with schizophrenia and CO-induced DNS after ineffective HBOT. Although the mechanism of the phenomenon is unclear, it can be possible reasons that the neuroprotective effect of donepezil and white matter insult by CO poisoning.